KETERPISAHAN ANTARA FAKTA FIKSI DAN FAKTA FAKTUAL: KRITIK ATAS NOVEL PEREMPUAN BERKALUNG SORBAN (PBS) KARYA ABIEDAH EL KHALIEQY - Anam, Miftakhul (Yinyang: Jurnal Studi Islam Gender dan Anak, 2010)
Novel Perempuan Berkalung Sorban (PBS) by Abiedah El Khalieqy have been created through a very subjective explorationthrough the assumptions that shaped suspicion. The novel as a whole illustrates idealitas Islamic educational institutions to replace theinstitutions that do injustice. Islamic School is so factually ideality in accordance with the novel, and the realities that are not in accordancewith these idealities purely fictional, born of a research capitalize gender prejudice and sentiment.